Can videoconferencing affect older people's engagement and perception of their social support in long‐term conditions management: a social network analysis from the Telehealth Literacy Project. (29th August 2016) - Banbury, Annie; Chamberlain, Daniel; Nancarrow, Susan; Dart, Jared; Gray, Len; Parkinson, Lynne
Abstract: Social support is a key component in managing long‐term conditions. As people age in their homes, there is a greater risk of social isolation, which can be ameliorated by informal support networks. This study examined the relationship between changes in social support networks for older people living in a regional area following weekly videoconference groups delivered to the home. Between February and June 2014, we delivered 44 weekly group meetings via videoconference to participants in a regional town in Australia. The meetings provided participants with education and an opportunity to discuss health issues and connect with others in similar circumstances. An uncontrolled, pre‐post‐test methodology was employed. A social network tool was completed by 45 (87%) participants either pre‐ or post‐intervention, of which 24 (46%) participants completed the tool pre‐ and post‐intervention. In addition, 14 semi‐structured interviews and 4 focus groups were conducted. Following the intervention, participants identified increased membership of their social networks, although they did not identify individuals from the weekly videoconference groups. The most important social support networks remained the same pre‐ and post‐intervention namely, health professionals, close family and partners. However, post‐intervention participants identified friends and wider family as more important to managing their chronic condition compared to pre‐intervention. Participants derived social support, in particular, companionship, emotional and informational support as well as feeling more engaged with life, from the weekly videoconference meetings. Videoconference education groups delivered into the home can provide social support and enhance self‐management for older people with chronic conditions. They provide the opportunity to develop a virtual social support network containing new and diverse social connections.